Diversity of Dragonflies (Odonata) at Pancur Resort Alas Purwo National Park, Indonesia - ABDU ROHMAN; DINDA PUTRI RAHMA DHARMAWAN; WACHJU SUBHAN; JEKTI PRIHATIN; VENDI EKO SUSILO; SELVI ARIYUNITA; BANDA NURHARA (Borneo Journal of Resource Science and Technology, 2022)
Alas Purwo National Park is one of the conservation areas located in the east of the island of Java. Dragonflies are crucial to the ecosystem’s equilibrium as predator, bioindicator, and vector for disease control. The sensitivity and presence of dragonflies affect the diversity of dragonflies in a habitat. This inventory can assist the Alas Purwo National Park with additional data and be a basis for making conservation policies. The study aimed to determine the type and diversity index of the dragonflies in this park. The sample location was determined using purposive sampling, and the sample conducted utilised road sampling. This research observed seven species: Orthetrum glaucum, Orthetrum chrysalis, Lathrecista asiatica, Potamarcha congener, Copera marginipes, Prodasineura autumnalis, and Nososticta insignis. The Libellulidae family had the most species; on the other hand, the Protoneuridae family had the fewest Shannon-Wiener diversity index (H’ = 1.6). Based on the criteria, the diversity index demonstrated moderate results. Pancur Resort Alas Purwo National Park provided a good environment and supported the survival of dragonflies.